THE MARGINALIZATION OF MODERN YOUTH IN THE CONTEXT OF SOCIAL CHANGE - Жураев, Жамшед (Центр Научных Публикаций (buxdu.uz), 2023)
This article analyzes the processes of marginalization of young people in the social structure and the processes of the emergence of marginal strata and statuses. The author describes and justifies the state of marginal status in the social structure of the modern community.